The effect of moderate levels of finely ground insoluble fibre on small intestine morphology, nutrient digestibility and performance of broiler chickens - Masoud Adibmoradi; Bahman Navidshad; Mohammad Faseleh Jahromi (Italian Journal of Animal Science, 2016)
This experiment was carried out to assess the following hypothesis: feeding broiler to fine insoluble fibre in the diet will result in improved gut morphology and enhanced performance. In this experiment, 200 broiler chickens in 20 pen cages with wood shaving-lined floors were exposed to five treatment groups with four pens/treatment: control diet, diets contained 0.75 or 1.5% barley hulls or diets contained 0.75 or 1.5% rice hulls in a completely randomised design with five treatment, four replicate and 20 chicks each. Type of fibre influenced the performance and digestive traits of broilers with effects varying in accordance with the level of fibre. Rice hulls inclusion consistently improved growth performance and crude protein (CP) digestibility in broilers regardless of dietary inclusion level (p < 0.05). However, barley hulls at 1.5% level improved crypt depth: villous height (VH) ratio and feed conversion ratio had an opposite effect on VH (p < 0.05). The beneficial effects of hulls were more obvious with the 1.5% dietary inclusion level than the 0.75% level. The useful effects of rice hulls inclusion on broiler efficiency was mainly because of its effect on CP digestibility while barley hulls at 1.5% level positively changed jejunum morphology. The data suggest that broilers may have a nominal requirement for insoluble fibre, however, the source and dietary inclusion rate of fibre might be important factors to satisfy dietary fibre requirements in birds.